Age-predicted maximal heart rate equations are inaccurate for use in youth male soccer players - Cicone, Z. S.; Sinelnikov, O. A.; Esco, M. R. (Pediatric Exercise Science, 2018)
Purpose: The purpose of this study was to compare the differences between measured (MHRobt) and predicted (MHRpred) maximal heart rate (MHR) in youth athletes. Methods: In total, 30 male soccer players [14.6 (0.6) y] volunteered to participate in this study. MHRobt was determined via maximal-effort graded exercise test. Age-predicted MHR (MHRpred) was calculated for each participant using equations by Fox, Tanaka, Shargal, and Nikolaidis. Mean differences were compared using Friedman`s 2-way analysis of variance and post hoc pairwise comparisons. Agreement between MHRobt and MHRpred values was calculated using the Bland-Altman method. Results: There were no significant differences between MHRobt and MHRpred from the Fox (P=.777) and Nikolaidis (P=.037) equations. The Tanaka and Shargal equations significantly underestimated MHRobt (P<.001). All 4 equations produced 95% limits of agreement of ±15.0 beats per minute around the constant error. Conclusions: The results show that the Fox and Nikolaidis equations produced the smallest mean difference in predicting MHRobt. However, the wide limits of agreement suggests that none of the equations adequately account for individual variability in MHRobt. Practitioners should avoid applying these equations in youth athletes and utilize a lab or field testing protocol to obtain MHR.